1996
DOI: 10.1577/1548-8667(1996)008<0052:coeast>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Control of ExternalAeromonas salmonicida: Topical Disinfection of Salmonids with Chloramine-T

Abstract: Brook trout Salvelimts fontinalis were treated with single 60-min static baths of 250 mg formalin/L. 3 r # NaCL and 15 mg Chloramine-T/L to evaluate the efficacy of these compounds against external infections of Aeromonas salmonicida. Prevalence of A. salmonicida was significantly lower in brook trout treated with Chloramine-T than among those treated with formalin or salt. Further laboratory tests substantiated the therapeutic value of a single treatment of Chloramine-"I' (15 mg/L) against A. salmonicida. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
7
1
1
Order By: Relevance
“…Furunculosis occurred in both tests of trial one and ERM occurred in one of two tests in trial one. Cipriano et al (1996b) reported that 9.0 ppm Chloramine-T inhibited A. salmonicida, but in this study the efficacy of Chloramine-T disinfection for either pathogen was not consistent. Although ERM did not occur following Chloramine-T disinfection, the pathogen was isolated from one biofilter after disinfection.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Furunculosis occurred in both tests of trial one and ERM occurred in one of two tests in trial one. Cipriano et al (1996b) reported that 9.0 ppm Chloramine-T inhibited A. salmonicida, but in this study the efficacy of Chloramine-T disinfection for either pathogen was not consistent. Although ERM did not occur following Chloramine-T disinfection, the pathogen was isolated from one biofilter after disinfection.…”
Section: Discussioncontrasting
confidence: 57%
“…If disease occurred when the system was restocked, fish were removed and a I-hour 10-ppm Chloramine-T (N-chloro-p-toluene sulfonamide sodium salt, Sigma Chemical Co., St. Louis, MO, USA) treatment of the entire recirculating system was carried out and the system restocked with char or rainbow trout. A concentration of 8.5 ppm Chloramine-T has been shown to be effective in controlling BGD (From 1980) and isolates of A. salmonicida were found to be inhibited by 9.0 ppm Chloramine-T (Cipriano et al 1996b). However, efficacy of Chloramine-T for disinfection of Yersinia ruckeri has not been reported.…”
Section: Pathogen Transmission and Disinfection Trialsmentioning
confidence: 99%
“…This is particularly the case for endemic infectious diseases of mucosal surfaces of terrestrial livestock (Meek et al, 1986;Van Donkersgoed, 1992;Gallo & Berg, 1995). Reflecting a similar paradigm, the use of prophylactic chemical bath treatments is an emerging routine practice in the high intensity farming of catfish (Bodensteiner et al, 1993) and various salmonid species Thorburn & Moccia, 1993;Cipriano et al, 1996). This emerging use pattern reflects:…”
Section: H E M O T H E R a P E U T I C A G E N T S ( M I C R O B I mentioning
confidence: 99%
“…The use of chloramine-T solutions for disinfection of water includes its use in aquaculture. Tests performed on brook trout by Cipriano et al [24] substantiated the therapeutic value of single treatment with chloramine-T (15 mg/L) against Aeromonas salmonicida, which was more successful than that treatment with formalin or salt.…”
Section: Disinfection Of Drinking Watermentioning
confidence: 99%